A Pilot Study of the Role of Mindfulness and Compassion in Parochial Empathy and Prosocial Behavior Toward Out-Groups - Denise Yiran Zheng (OSF Registries, 2021)
Denise Zheng's Master's thesis pilot study.
Keywords: Social Psychology; Social and Behavioral Sciences; Psychology; compassion; empathy; intergroup; mindfulness; prosocial